2019 Social Accounting Matrix for Colombia - International Food Policy Research Institute; Bioversity International (International Food Policy Research Institute, 2024)
The Nexus Project is a collaboration between IFPRI and its partners, including national statistical agencies and research institutions. Our aim is to improve the quality of social accounting matrices (SAMs) used for computable general equilibrium (CGE) modeling. The Nexus Project develops toolkits and establishes common data standards, procedures, and classification systems for constructing and updating national SAMs. The 2019 Colombia SAM follows the Standard Nexus Structure. The open access version of the Colombia SAM separates domestic production into 42 activities. Factors are disaggregated into labor, agricultural land, and capital. Labor is further disaggregated across three education categories. Representative households are disaggregated by rural and urban areas and by per capita expenditure quintile. The remaining accounts include enterprises, government, taxes, savings-and-investment, and the rest of the world.